SERVICE QUALITY MEASUREMENT IN HOTEL INDUSTRY - B.Lhamtseden,; M.Bilegsaikhan,; E.Tsomorlig, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Given the increasing competitive phenomenon of the hospitality industry, this research assessed the expectations and perceptions of service quality in Mongolia’s four and five stars hotels by applying a modified version of the SERVQUAL model. A convenient sample of 472 guests drawn from six 4,5 star hotels was used in the analytical stage. It also examined the relationship between overall satisfaction levels and the five service quality dimensions reliability, responsiveness, assurance, empathy end tangibility. The findings indicated, as a whole that the hotel customers’ perceptions of service quality provided by the hotel industry were lower than their expectations and the gap between customers’ expectations and perceptions were significant.